Point-based and model-based geolocation analysis of airborne laser scanning data - Sefercik, Umut Gunes; Buyuksalih, Gurcan; Jacobsen, Karsten; Alkan, Mehmet (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2017)
Airborne laser scanning (ALS) is one of the most effective remote sensing technologies providing precise three-dimensional (3-D) dense point clouds. A large-size ALS digital surface model (DSM) covering the whole Istanbul province was analyzed by point-based and model-based comprehensive statistical approaches. Point-based analysis was performed using checkpoints on flat areas. Model-based approaches were implemented in two steps as strip to strip comparing overlapping ALS DSMs individually in three subareas and comparing the merged ALS DSMs with terrestrial laser scanning (TLS) DSMs in four other subareas. In the model-based approach, the standard deviation of height and normalized median absolute deviation were used as the accuracy indicators combined with the dependency of terrain inclination. The results demonstrate that terrain roughness has a strong impact on the vertical accuracy of ALS DSMs. From the relative horizontal shifts determined and partially improved by merging the overlapping strips and comparison of the ALS, and the TLS, data were found not to be negligible. The analysis of ALS DSM in relation to TLS DSM allowed us to determine the characteristics of the DSM in detail. (C) 2016 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: airborne laser scanning; terrestrial laser scanning; height; digital surface model; accuracy; DIGITAL ELEVATION MODELS; LIDAR DATA; ACCURACY ASSESSMENT; DEM GENERATION; METHODOLOGY; TARGETS; SLOPE; Optics